Visualizing Religious Moderation in Indonesia: A Cultural Semiotic Analysis of MORA Award-Winning Short Films - Fuad Hasyim; Joni Rusdiana; Arroyan Ramly (UIN Raden Mas Said Surakarta, 2026)
This study examines the narrative construction of religious moderation in three award-winning short films from the Ministry of Religious Affairs’ 2021 Religious Moderation Short Film Competition: Mabbere, Setetes Embun Malam, and Balas Dendam Terbaik. Using a descriptive qualitative approach and Roland Barthes’ cultural semiotic framework, this study analyzes nine selected scenes through denotation, connotation, and myth. The findings show that the films construct religious moderation as a visual-textual ethic embedded in everyday practices, including food sharing, interfaith assistance, community work, crisis solidarity, apology, and reconciliation. Mabbere represents accommodation of local culture and tolerance through Buginese culinary practice and halal sensitivity. Setetes Embun Malam visualizes national commitment and tolerance through interfaith cooperation in public facility development. Balas Dendam Terbaik articulates non-violence and tolerance through humanitarian care during the COVID-19 crisis. These representations manifest Inclusive Muamalah and Ukhuwah Basyariyah as socioreligious practices connecting faith commitment with social responsibility.